(untitled) (Journal of the College of Basic Education, 2023)
From the foregoing, we conclude that this study took its importance in the field of studying the methodology of resources through the systematic formulation of some narrations using some words and expressions to indicate that. Sometimes he relies on the same approach as the historians who preceded him, and sometimes he deviates from that approach, as he relies on direct quotation of texts, or he varies in his approach in mentioning the name of the author and his owner, and he tries to deal with the novel on the basis of diversifying its authority. He dealt with the narrations that he quoted from his sheikhs, using the terms of the hadith scholars in that regard.